[PP.05.10] BLOOD PRESSURE LOWERING AND SELF-REPORTED ADHERENCE WITH A FIXED-DOSE COMBINATON OF PERINDOPRIL/AMLODIPINE IN PRIMARY CARE: A NON-INTERVENTIONAL STUDY. (September 2017) - Limbourg, F.P.; Weger, B.; Haller, H.
Abstract : Objective: To investigate the effect on blood pressure (BP) and adherence to medication after 3 months of therapy with a fixed-dose combination of Perindopril/Amlodipine (PER/AMLO, 3.5/2.5 mg or 7/5 mg) in hypertensive patients. Design and method: We performed a prospective, non-randomized study on the effect of 3 months of therapy with single-pill PER/AMLO medication in patients with hypertension who were previously untreated or required a change in medication. Changes in BP were assessed by office BP, home BP, and 24-h BP monitoring. Adherence was measured with the Hill-Bone medication adherence scale. Results: 1814 patients (830 women, 45, 8%) were enrolled, mean age was 60.0 years, 16.5% were older than 75 years, mean body mass index was 28.9 kg/m 2 . 1770 patients completed the 3 months follow-up, 46.0% of patients were previously untreated. Home BP was available from 1279 patients, 24-h BP was available from 167 patients. Hill-Bone questionnaire at 3 months was available from 92.4% of patients. 97.7% of patients were initiated with 3.5/2.5 mg PER/AMLO, 34.7% were up-titrated to 7/5 mg after a mean time of 32.9 days. 68.5% of patients had no other antihypertensives, the most prevalent co-medication were betablockers (22%). After 3 months of therapy, office systolic BP (SBP) decreased from 163.6 ± 14.8 to 133.6 ± 11.9 mmHg and diastolic BP (DBP) from 95.4 ± 9.4 to 80.3 ± 7.7 mmHg (p < 0.0001 for all BP changes). Hypertension control rate with PER/AMLO was 72.3%, overall response rate was 69.1%. Home SBP decreased from 160.6 ± 14.9 to 130.9 ± 11.8 mmHg and DBP from 93.6 ± 9.5 to 79.4 ± 7.6 mmHg (p < 0.0001). 24-h SBP decreased from 150.6 ± 12.6 to 132.4 ± 11.9 mmHg and DBP from 88.9 ± 8.8 to 79.4 ± 8.5 mmHg. Mean daytime SBP/DBP decreased from 157.80 ± 13.23/92.65 ± 9.49 mmHg to 138.03 ± 12.37 /82.40 ± 8.76 mmHg. Mean nighttime SBP/DBP decreased from 141.77 ± 14.29/83.49 ± 10.60 mmHg to 124.60 ± 13.06/74.53 ± 9.72 mmHg (p < 0.0001). Perfect adherence (all questions of the scale answered with 'none of the time') at 3 months was 47.2%, and perfect adherence among pretreated patients improved from 20.6% to 43.6% after 3 months. Conclusions: PER/AMLO in single-pill combinations can be successfully used in patients with hypertension previously untreated or unsuccessfully treated and shows significant improvement in adherence.